Dry eye specific quality of life in veterans using glaucoma drops. Issue 3 (June 2015) - Camp, Andrew; Wellik, Sarah R.; Tzu, Jonathan H.; Feuer, William; Arheart, Kristopher L.; Sastry, Ananth; Galor, Anat
Abstract: Purpose: To evaluate the frequency of ocular surface symptoms and their potential impact on dry eye specific quality of life (QoL) in patients using versus not using glaucoma medications. Material and methods: The study was a single-center, cross-sectional survey of patients seen at the Miami Veterans Affairs (VA) ophthalmology and optometry clinics from June to August, 2010. Patients were invited to complete the Dry Eye Questionnaire 5 (DEQ5) and the Impact of Dry Eye on Everyday Life (IDEEL) at their visit. Of 1348 patients seen in the Miami VA eye clinics during this three-month period, 467 patients completed the DEQ5 and 391 responded to both questionnaires. Outcome measures comprised ocular surface symptoms and their impact on dry eye specific QoL in patients using versus not using glaucoma drops. Results: An increasing number of glaucoma drops was significantly associated with an increased percentage of severe dry eye symptoms: no medications, 25% ( n  = 89/353); 1 or 2 medications, 27% ( n  = 17/62); 3 or more medications, 40% ( n  = 21/52); p  = 0.03 (Armitage's test for linear-trend in proportions). There was an association between increasing number of drops and decreasing emotional well-being scores (linear p  < 0.001; quadratic p  = 0.029). Black patients had higher dry eye symptoms and lower emotional QoL scores compared to white patients at every level of medication use. Conclusion: An increasing number of glaucoma medications were associated with an increased frequency of severe dry eye symptoms and decreased emotional QoL. Additionally, dry eye specific emotional QoL was more severely affected in black versus white patients.